Electrochemical Studies for Cation Recognition with Diazo-Coupled Calix[4]arenes - Bongsu Kim; Tae Hyun Kim (Journal of Analytical Methods in Chemistry)
The electrochemical properties of diazophenylcalix[4]arenes bearing ortho-carboxyl group (o-CAC) and ortho-ester group (o-EAC), respectively, in the presence of various metal ions were investigated by voltammetry in CH3CN. o-CAC and o-EAC showed voltammetric changes toward divalent metal ions and no significant changes with monovalent alkali metal ions. However, o-CAC preferentially binds with alkaline earth and transition metal ions, whereas no significant changes in voltammetric signals are observed in o-EAC with alkaline earth metal ions. o-EAC only binds with other transition metal ions. This can be explained on metal ion complexation-induced release of proton from the azophenol to the quinone-hydrazone tautomer followed by internal complexation of the metal ion with aid of nitrogen atoms and ortho-carbonyl groups in the diazophenylazocalix[4]arenes.